2016
DOI: 10.1016/s1470-2045(16)30120-6
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and quality of life after adjuvant chemoradiotherapy versus radiotherapy alone for women with high-risk endometrial cancer (PORTEC-3): an open-label, multicentre, randomised, phase 3 trial

Abstract: Dutch Cancer Society, Cancer Research UK, National Health and Medical Research Council, Project Grant, Cancer Australia Grant, Italian Medicines Agency, and Canadian Cancer Society Research Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
210
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(258 citation statements)
references
References 37 publications
14
210
4
1
Order By: Relevance
“…High insulin levels and obesity are independent risk factors for estrogen-related type I endometrial endometrioid carcinomas (2). At present, surgery combined with adjuvant progesterone therapy or postsurgical radiotherapy is the predominant treatment strategy for endometrial cancer (3). However, certain patients also suffer cancer recurrence and metastasis, rendering the prognosis poor (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High insulin levels and obesity are independent risk factors for estrogen-related type I endometrial endometrioid carcinomas (2). At present, surgery combined with adjuvant progesterone therapy or postsurgical radiotherapy is the predominant treatment strategy for endometrial cancer (3). However, certain patients also suffer cancer recurrence and metastasis, rendering the prognosis poor (3).…”
Section: Introductionmentioning
confidence: 99%
“…At present, surgery combined with adjuvant progesterone therapy or postsurgical radiotherapy is the predominant treatment strategy for endometrial cancer (3). However, certain patients also suffer cancer recurrence and metastasis, rendering the prognosis poor (3). For effective cancer prevention and treatment, it is necessary to identify critical genetic changes that initiate endometrial cancer and contribute to its progression (4).…”
Section: Introductionmentioning
confidence: 99%
“…These data are of additional value to the results of the ongoing randomized trials of adjuvant treatment in high-risk EC. 10,11 …”
Section: Discussionmentioning
confidence: 99%
“…7Y9 Whether adjuvant chemotherapy and/or chemoradiation will improve the outcome of early stage high-risk endometrioid type endometrial carcinoma is the question of interest in the PORTEC III (NCT00411138) and the GOG-249 (NCT00807768) studies. 10,11 Although randomized controlled trials (RCTs) are superior to observational studies with respect to the level of evidence, selection bias might influence results of both types of studies. Because patients with endometrial carcinoma are often elderly women with comorbidities, these patients might be frequently excluded from participating in studies that randomize conventional treatment with more aggressive treatment.…”
mentioning
confidence: 99%
“…Pelvic external beam radiotherapy has been the standard adjuvant treatment for patients with high-risk endometrial cancer for several decades (27). Randomised trials comparing adjuvant chemotherapy and external beam radiotherapy showed similar rates of survival (28,29).…”
Section: Lymphovascularmentioning
confidence: 99%